Endotropia acomodativa en paciente de 18 meses de edad. - Yánez Naranjo, Kelvin Jaffet (2021)
The present case. An 18-month-old female pediatric patient who comes to the consultation with her mother for denoting that she deviates her left eye when performing activities or looking at things fixedly for a week, the mother also refers that she does not function normally. It makes it difficult for her to walk and she just wants to be held or accompanied. At the first external observation of the patient, we found an endotrophic deviation in the left eye, little availability to stimuli that call her attention and with separation anxiety. The methodology of this case was carried out by reviewing the patient's clinical history, both personal history (APP) and family history (APF), examinations such as fundus, retinoscopy under controlled cycloplegia under ophthalmological care, biomicroscopy, cover test and the related to determine an exact diagnosis and choose the best treatment for the patient. In conclusion, the cause of the deviation was determined by ruling out other causes of endotrophic or general deviations such as a deprivation endotrophic , presentation of incomitant endo-deviations, pseudo endotrophic or a basic or acquired endotrophic , diagnosing an accommodative or refractive endotrophic due to elevated hyperopia thanks to the result of retinoscopy. which gave us high values.